The industrial revolution 4.0 in Malaysia: challenges, barriers, obstacles, and recommendations for action - Wong, Boon Jian; Loke, Wei Yun; Kong, Siao Ching; Mak, Pui Jun; Lim, Yee Lian (2020)
The global trend of adopting Fourth Industrial Revolution is accelerate but Malaysia still not widely implemented it. This research is aimed to examine the reasons affecting the Industry to adopt Fourth Industrial Revolution in Malaysia. Fourth Industrial Revolution and five independent variables which are Technology Acceptance (TA), Awareness (AW), Finance Resource (FR), Appropriate Competence and Skill (ACS) and Government Policies (GP) has been adopted in this research. This research has used questionnaire method to collect relevant data. The questionnaire designed consists of 42 questions and a total of 385 sets of responses were collected. Smart PLS 3 software has been used to analyse the result. Of the five independent variables, it was found that TA, ACS, FR are significantly influence the industry to adopt Fourth Industrial Revolution. However, AW and GP shown an insignificant relationship with the industry to adopt Fourth Industrial Revolution in Malaysia. This study has discussed about the policies aiming towards helping the industry to adopt Fourth Industrial Revolution in Malaysia such as provide training and education, provide incentive and funding, create regulatory framework as well as conduct Industry 4.0 campaign for entrepreneurs. The limitation of this research is measurement of barrier to adopt Fourth Industrial Revolution, this study was used cross-sectional data only, and the data obtained is not available to defined all the barriers occur in others developing countries.